2022
DOI: 10.3390/pathogens11060641
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Inhibits Inflammation and Gastric Damage during H pylori Infection by Targeting NF-kB–miRNA Axis

Abstract: Helicobacter pylori (H. pylori) infection is considered as one of the strongest risk factors for gastric disorders. Infection triggers several host pathways to elicit inflammation, which further proceeds towards gastric complications. The NF-kB pathway plays a central role in the upregulation of the pro-inflammatory cytokines during infection. It also regulates the transcriptional network of several inflammatory cytokine genes. Hence, targeting NF-kB could be an important strategy to reduce pathogenesis. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The transcription factor NF-κB is one of the major mediators of the inflammatory response against H. pylori infection [ 75 ]. H. pylori activates NF-κB through the canonical pathway, namely IKK complex phosphorylation/degradation of the IκB inhibitor, leading to the nuclear translocation of NF-κB, and thereby resulting in the acceleration of its target genes [ 15 , 68 , 76 ]. In this study, we showed that KP reduced the phosphorylation of IκBα and p65, thereby repressing the translocation of p65 from the cytosol to the nucleus in H. pylori -infected gastric mucosal injury mice.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor NF-κB is one of the major mediators of the inflammatory response against H. pylori infection [ 75 ]. H. pylori activates NF-κB through the canonical pathway, namely IKK complex phosphorylation/degradation of the IκB inhibitor, leading to the nuclear translocation of NF-κB, and thereby resulting in the acceleration of its target genes [ 15 , 68 , 76 ]. In this study, we showed that KP reduced the phosphorylation of IκBα and p65, thereby repressing the translocation of p65 from the cytosol to the nucleus in H. pylori -infected gastric mucosal injury mice.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori , Sydney Strain SS1 ( cagA + , vacA s2m2) were grown on brain heart infusion (BHI) agar (Difco, USA) containing 7% heat-inactivated horse serum (Invitrogen), antibiotics, and IsoVitaleX as mentioned previously (Saha et al 2022 ). Plates were kept in a microaerophilic atmosphere at 37 °C for five to six days.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of week 4, all mice were sacrificed. Gastric tissues were isolated and blood was collected for experimental purposes as described previously (Saha et al 2022 ). Experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…H. pylori , Sydney Strain SS1 (cagA+, vacA s2m2) were grown on brain heart infusion (BHI) agar (Difco, USA) containing 7% heat-inactivated horse serum (Invitrogen), antibiotics and IsoVitaleX as mentioned previously (33). Plates were kept in a microaerophilic atmosphere at 37°C for five to six days.…”
Section: H Pylori Culturementioning
confidence: 99%